Becoming a first-time father during the COVID-19 pandemic in France - Jean-Dit-Pannel, Romuald; Belot, Rose-Angélique; Mellier, Denis; Robert, Laura; Petersen, Célia; Dinet, Benoît; Bréhat, Cécile; Koliouli, Flora (Frontiers in Psychiatry, 2024)
The role of fathers in Western societies has undergone significant change over time. However, their psychopathology remains largely misunderstood and difficult to identify. This study aims to explore the lived experiences of first-time fathers during the COVID-19 pandemic. Twenty-seven first-time French fathers were recruited for the study, which involved a narrative interview, the Rorschach projective test, the Edinburgh Postnatal Depression Scale (EPDS), and a semi-structured interview. Narrative interviews revealed several challenges faced by these fathers, including the pressure of paternal responsibility, the need to be actively involved in the prenatal activities and caregiving (haptonomy, skin-to-skin contact), and concerns about the future of their couple and family as a triad. The Rorschach tests showed numerous perinatal responses and difficulties in identifying phallic representations among the fathers. Additionally, the EPDS scores indicated that 15% of fathers showed signs of depression, while 52% exhibited signs of anxiety. This study also examines the impact of the COVID-19 pandemic and its associated health context on creating the initial triad. Lastly, the case of one father is presented to illustrate the need for diagnostic tools to address the psychopathology of fathers, as narrative or semi-structured interviews have often fallen short of addressing this issue.